Ministerial Decree No. 860/2012 amending ministerial decree No. 296/2009 concerning the re-regulation of the rules and procedures of pharmaceuticals registration / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 72/2012